The Consultant's Quick Start Guide - Biech, Elaine (Ascent Audio, 2019)
An action plan for working as a consultant Management consulting is a USD250 billion industry and growing at a rate of over four percent annually. Many predict that more than 40 percent of the U.S. workforce will soon be contingent, freelance, or consulting members of the workforce-making this book more relevant than ever. Individuals become independent consultants out of necessity or preference: necessity because they lost their job or the company offered an attractive exit package; preference because they want a career change, more control over their time, or an enriched, varied work situation. Consulting also appeals to the Millennial workforce who are searching for careers that offer a good salary as well as meaningful work. The New Consultant's Quick Start Guide: - Serves as a companion to The New Business of Consulting - Provides you with a place to plan your transition into consulting - Helps you identify your niche, develop a business plan, charge what you're worth, and create a marketing strategy to ensure a steady stream of clients - Prepares you for changes you will encounter beyond your professional life, including social, family, and financial aspects.
Online resource; Title from title page (viewed July 30, 2019)
Keywords: Business; Affaires; Audiobooks